Changes in Climatology, Snow Cover, and Ground Temperatures at High Alpine Locations - Bender, Esther; Lehning, Michael; Fiddes, Joel (Frontiers in Earth Science, 2020)
Knowledge about changes in ground temperatures under a changing climate are important for many environmental, economic and infrastructure applications and can be estimated by transient numerical simulations. However, a full annual cycle of precipitation data is needed to achieve this, yet is often unavailable in high alpine regions where a lack of infrastructure precludes installation of heated instruments capable of measuring the solid precipitation component. This paper presents a method to reconstruct a full year precipitation dataset at high alpine weather stations, which is then used to model ground temperature and snow depth for 16 alpine sites in Switzerland for the past and three climate scenarios. Differences in the possible temperature trajectories are highlighted with a focus on elevation and regional climatic differences within Switzerland. Snow height and ground temperatures under a changing climate are modelled with the one- dimensional physical model SNOWPACK by applying a delta change signal to the meteorological data set obtained from the CH2011 climate scenarios of Switzerland. All sites showed a decrease of snow cover, a shortening of the snow season and an increase in ground temperature to the end of the century. Sites in the inner alpine regions of Grisons were found to be less sensitive to climate change than sites in the western Alps. The magnitude of reduction of mean snow height depends mainly on location, whereas for the contraction of the snow season elevation is the key factor. It could be shown that the temperature - precipitation combination as expressed in the snow dynamics explain changes in ground temperatures more than the individual changes in either parameter. Alpine meadow and thin snow cover appear to delay warming of the ground.